2019
DOI: 10.1016/j.jconrel.2018.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage entrapped silica coated superparamagnetic iron oxide particles for controlled drug release in a 3D cancer model

Abstract: 28Targeted delivery of drugs is a major challenge in treatment of diverse diseases. Systemically 29 administered drugs demand high doses and are accompanied by poor selectivity and side 30 effects on non-target cells. Here, we introduce a new principle for targeted drug delivery. It is 31 based on macrophages as transporters for nanoparticle-coupled drugs as well as controlled 32 release of drugs by hyperthermia mediated disruption of the cargo cells and simultaneous 33 deliberation of nanoparticle-linked drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Magnetic nanoparticles are already versatilely used in research and partly in clinical issues for hyperthermia or drug delivery in tumor [31][32][33][34][35] and infection treatment [36,37], as contrast agents for magnetic resonance imaging [38][39][40], and others [41,42]. The biocompatibility of certain magnetic nanoparticles with different composition, magnetic properties or size has already been published [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles are already versatilely used in research and partly in clinical issues for hyperthermia or drug delivery in tumor [31][32][33][34][35] and infection treatment [36,37], as contrast agents for magnetic resonance imaging [38][39][40], and others [41,42]. The biocompatibility of certain magnetic nanoparticles with different composition, magnetic properties or size has already been published [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…[ 47 ] These NPs have been utilized alone [ 48 ] or in combination with other nanoparticulate systems for additional functionality. [ 49 ] Zhang et al. reported a silica core–silica shell platform for postponing drug release from the M ϕ s, so that M ϕ s will have enough time to home into the cancer tissue, avoiding off‐target toxicities.…”
Section: Ex Vivo Manipulated Alive Immune Cellsmentioning
confidence: 99%
“…It was revealed that incorporating albumin–PTX conjugate within mesoporous silica NPs could increase its uptake efficiency by M ϕ s. Transwell migration assay confirmed an enhanced migration ability of loaded M ϕ s toward breast cancer cells. [ 49b ]…”
Section: Ex Vivo Manipulated Alive Immune Cellsmentioning
confidence: 99%
“…Ullah et al used the rapid macrophage endocytosis of silica-coated SPIONs loaded with maytansin, an antiproliferative toxin. They infiltrated these macrophages in spheroids of tumor cells and destroyed the cells by hyperthermia in vitro [ 125 ]. Moghimi et al [ 124 ] found that liposomes and polymeric nanospheres used as nanocarriers are also opsonized, which promotes their clearance by macrophage activation.…”
Section: Reviewmentioning
confidence: 99%